Encounters: themes in literature - Carlsen, G. Robert (New York, Webster Division, McGraw-Hill, 1973)
A thematically arranged anthology of poems, short stories, plays, and novellas for the tenth-grade reader.
Keywords: Literature -- Collections; Literature -- Collections